2008
DOI: 10.1080/08820530802049962
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Toxicity of Hydroxychloroquine

Abstract: This review summarizes the current literature regarding the ocular complications of hydroxychloroquine. Hydroxychloroquine has been used since the 1950s for the treatment of various rheumatic and dermatologic diseases. Hydroxychloroquine can cause ocular toxicity, with the most serious being an irreversible retinopathy. At the present time, no "gold standard" exists for identification of the ocular toxicity prior to its development. This has led to controversy regarding the recommendations for ophthalmologic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 39 publications
2
55
0
8
Order By: Relevance
“…Ophthalmoscopic examination may reveal granular pigmentary changes in the form of bull's-eye maculopathy with a circle of RPE atrophy surrounding the central fovea. 12 It was demonstrated that high-speed ultra-high resolution OCT was able to detect the loss of the perifoveal photoreceptor inner segment/ outer segment junction and thinning of the outer nuclear layer in patients receiving HCQ. 13 Retinal thinning was considered to be the earliest indicator of retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Ophthalmoscopic examination may reveal granular pigmentary changes in the form of bull's-eye maculopathy with a circle of RPE atrophy surrounding the central fovea. 12 It was demonstrated that high-speed ultra-high resolution OCT was able to detect the loss of the perifoveal photoreceptor inner segment/ outer segment junction and thinning of the outer nuclear layer in patients receiving HCQ. 13 Retinal thinning was considered to be the earliest indicator of retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, CQ and its derivative hydroxychloroquine are widely used as late-stage autophagy inhibitors and have been evaluated in several Phase I and II clinical trials in combination with chemotherapy drugs in a variety of tumor types [13,14]. However, the safety concerns, including ocular toxicity and irreversible retinopathy limit their clinical use, and thereby it is highly desirable for new inhibitors of autophagy [15].…”
mentioning
confidence: 99%
“…Tehrani hace una revisión de los diferentes protocolos propuestos y encuentra grandes diferencias entre ellos 36 . El laboratorio responsable de la fabricación de HCQ recomienda un control a todos los pacientes cada 3 meses 33 .…”
Section: Recomendaciones De Cribadounclassified
“…Tehrani en su artículo de 2008 recomienda que en el caso de detectar una maculopatía posible, el paciente puede ser seguido cada 3 meses hasta decidir si se trata de toxicidad y retirar el fármaco o si no y mantenerlo. En caso de una probable, el fármaco debe ser retirado por el internista lo antes posible y una vez retirado, debemos revisar al paciente cada 3 meses hasta que se estabilice la progresión del daño 36 .…”
Section: Recomendaciones De Cribadounclassified
See 1 more Smart Citation